2020
DOI: 10.3390/min10111013
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of Iron, Copper, Lead, and Zinc from the Sludge Mining Sediment at Different Particle Sizes, pH, and Pulp Density Using Acidithiobacillus ferrooxidans

Abstract: Globally, the amounts of metal ore deposits have been declining, so the research directions investigating the extraction of metals from materials that are classified as waste are gaining more importance every year. High concentrations of Cu, Pb, Zn, and Fe were analyzed in the sludge sediment (Zlaté Hory, Czech Republic), which is a waste product of the mining industry. In the bioleaching process, bacterial cells have been established as being able to convert metals from solid to liquid phase. However, the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…Rouchalova (2020) pointed out that particle size (71–100 μm), pH (1.8) and microorganism density (9K medium) are the most important parameters in achieving high depollution yields [ 31 ]. Groudev et al (2001) pointed out that microbial activity is the most important factor in Cu, Zn, Cd and As bioleaching, the exception being Pb [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rouchalova (2020) pointed out that particle size (71–100 μm), pH (1.8) and microorganism density (9K medium) are the most important parameters in achieving high depollution yields [ 31 ]. Groudev et al (2001) pointed out that microbial activity is the most important factor in Cu, Zn, Cd and As bioleaching, the exception being Pb [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the literature have shown that bioleaching is efficient for the extraction of metals from water treatment sludge (Cr 92.6%, Cu 80.6%, Fe 95.6%, Mg 91%, Ni 89.7%, Pb 99.5%, Zn 93% [ 33 , 34 , 35 ], Fe 76.5%, Cu 82%, Pb 89.9%, Zn 90%) [ 31 ] or from municipal and industrial waste [ 36 ]. Pyrotite bioleaching could increase Fe recovery by bacterial adaptation and biological contact oxidation [ 37 ], and Fe can be removed (18%) by adding 9K medium [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that by decreasing the particle size, the specific surface area increases, and leaching is enhanced both by kinetics and yields [10][11][12] (Torma et al, 1972, Torma et al, 1977, Miller et al, 1999. However, results showing no clear benefits regarding additional milling have also been reported [13]. Moreover, too fine of a particle size has been considered inhibitory to bioleaching microorganisms (reviewed in [14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods to study particle sedimentation: the bottom suction pipe method based on the Oden theory [10,11], repetition depth pipette method based on the McLaughlin formula [12,13], and sand sink method to study the effect of flow turbulence on the particle settling rate [14][15][16]. Some studies were conducted to perform sedimentation tests on a sediment suspension in a sedimentation cylinder, and formulae for the sedimentation rate were obtained [17,18]. Other studies analyzed experimental data to design a conical settlement cylinder and establish a settlement rate formula for nonuniform sand groups [19].…”
Section: Introductionmentioning
confidence: 99%